Hotel Management System and Innovative Organization - Duangkamol Pongphankae ดวงกมล ผ่องพรรณแข; Teerawat Chantuk ธีระวัฒน์ จันทึก (Dusit Thani College Journal, 2018)
This paper aimed to 1) study and review the basic knowledge about concepts of hotel management system, organization and providing service 2) study and review basic of innovation classifications and capability of entrepreneurs 3) the proposed framework of hotel management system focuses on innovative organizations. The study was based on review the relevant literature in order to gain the basic principle the cognitive framework concept hotel management system, which focuses on innovative organizations. In order to achieve that concept, the linked of innovative organization should be occurred in the organization.